Resistance and effective power on various casco models of purse seiner - St Aisjah Farhum; Ilham Jaya; . Karliani (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
This study aimed to find out the magnitude of resistance and effective power onthe three casco models of purse seiner i.e. round bottom, round flat-bottom and U-V bottom. In the present study, we employed a numerical simulation using Holtrop and Mennenn method. To get the values of motion resistance and effective power on various purse seiner, it was used the purse seiner speed of 0-12 knot. We developed the simulation using 12 purse seiner sampling data which were operating in Makassar Strait. Simulation results indicated that the increasing main dimension of purse seiner was proportional to the increasing the magnitude of resistance and effective power. This study suggested that the round flat of casco model has greater resistance compared with the other casco model for purse seiner operating in Makassar Strait.